The influence of social dominance, ambivalent sexism and organizational climate towards sexual harassment tolerance / Ahmad Shazeer Mohamed Thaheer …[et al.] - Mohamed Thaheer, Ahmad Shazeer; Sani, Azurin; Abdul Rahim, Abdul Rahman; Abdullah, Mohammad Hakimy; Purhanudin, Noorfaiz; Zamaruddin, Nor Amizatul Akma (Universiti Teknologi MARA, 2021)
As the participation of women in the workforce has grown over time, sexual harassment at the workplace has received much attention among scholars. Even though this topic is famous, the study about tolerance level among women is still lacking and needs more discussions nowadays. There have been some changes from several aspects such as social, economic, culture, and legislation for the last ten years. Several factors could affect the level of tolerance towards sexual harassment among women. Therefore, this paper aims to examine the effects of social dominance, ambivalent sexism, and organizational climate regarding women's tolerance towards sexual harassment at the workplace. The finding revealed that women's tolerance for sexual harassment is positively related to ambivalent sexism, workplace atmosphere, and social dominance. Additionally, aggressive sexism is the strongest predictor of women's tolerance for sexual harassment. This study implies that creating awareness on tolerance and removing harassment from the workplace requires action against individual incidents and existing practices and attitudes that foster sexual harassment.